Masa Keemasan Pendidikan Islam (Studi Tentang Peran Khalifah Harun Al - Rasyid Dalam Pendidikan Islam) - Ali Mustofa (Jurnal Pendidikan Islam, 2018)
Abstract: The role of the Caliph Harun al - Rasyid in Isl amic education is very large, including creating a varied curriculum that not only focuses on the problems of religion that are adapted to the level of education, establishing Khizanah al - Hikmah as an institution of translation, observation and reading roo m, building educational institutions , guaranteeing the lives of high - paying educators, utilizing the country's wealth to build educational infrastructure facilities, cooperating with developed countries to exchange information about science, developing le arning systems by developing Islamic education goals. Scientific treasures really grew rapidly in Baghdad under the rule of Caliph Harun al - Rashid. The era of Caliphate Harun al - Rasyid was a golden age in various fields, ranging from the fields of governme nt, socio - economic, administration, and the most prominent of science.